HUBUNGAN KECUKUPAN GIZI DENGAN STATUS GIZI BALITA - Imelda Feneranda Seravia Tambi (Jurnal Keperawatan Dirgahayu (JKD), 2019)
Nutritional adequacy needed by all group of ages, one of them is toddlers and nutritional adequacy can be illustrated through nutritional status. Toolders have a significant need for nutrients that support growth and provide energy. The design of this study was correlation study. Population of this study was toddlers in IHC Sedap Malam Bumiarjo RW 05. The technique was used random sampling of 35 respondents. Data were collected by filling the 24-hour food recall observation sheet and measuring the anthropometric of height and weight. From the statistic test result of Rank Spearman used the SPSS 16 program, it showed that p = 0,011, p < 0,05 then H0 was rejected, with rs +0,425 which means that there is a moderate positive strength relationship between nutritional adequacy and nutritional status in toddlers. Nutrition have an important role to improve the nutritional status. Therefore, the researcher suggests to improve IHC programs in the field of nutrition such as healthy toddler competitions dan counseling.